2018
DOI: 10.1186/s40795-018-0249-4
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional risk and associated factors of adult in-patients at a teaching hospital in the Copperbelt province in Zambia; a hospital-based cross-sectional study

Abstract: Background: Nutritional risk and undernutrition are common problems among medical and surgical patients. In hospital, malnutrition is frequently under-diagnosed and untreated thereby contributing to morbidity and mortality. The purpose of this study was to determine the prevalence of nutritional risk among adult inpatients at a teaching hospital in Zambia. In addition, the study sought to establish factors associated with nutritional risk. Methods: A hospital-based cross-sectional study comprising of 186 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Although a wide age-range was included, the median age of the patients (43 years) was at least a decade younger than those reported for similar studies done in Europe, ranging between 57–72 years [1,2,8,15,20,21]. It is closer to the mean ages of similar studies conducted on the African continent which reported a mean age of 34 years (Burundi) [27], 37 years (Uganda) [3], 41 years (Zambia) [28], 47 years (Cameroon) [29], and 48 years (South Africa) [6], highlighting the differences in patient profiles between continents.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Although a wide age-range was included, the median age of the patients (43 years) was at least a decade younger than those reported for similar studies done in Europe, ranging between 57–72 years [1,2,8,15,20,21]. It is closer to the mean ages of similar studies conducted on the African continent which reported a mean age of 34 years (Burundi) [27], 37 years (Uganda) [3], 41 years (Zambia) [28], 47 years (Cameroon) [29], and 48 years (South Africa) [6], highlighting the differences in patient profiles between continents.…”
Section: Discussionsupporting
confidence: 46%
“…Using a different tool (MUST), another study from South Africa reported a risk of malnutrition of 72.3% [6]. Data from Zambia [28] reported a 59.7% and Uganda [3] a 25–59% prevalence. Hospital malnutrition (defined as ≥10% weight loss from usual weight) was reported to be 47.3% in Burundi [27] and data from Cameroon (defining malnutrition as BMI < 18.5 kg/m 2 , and/or MUAC < 22 cm for women and 23 cm for men) reported 19.3% [29].…”
Section: Discussionmentioning
confidence: 99%
“…In Africa, 25 to 72.3% of hospitalized patients are at risk for malnutrition [ 1 , 2 , 3 ]. Hospital malnutrition is a concern globally, however there are limited studies on the prevalence of hospital-based malnutrition in low resource countries, like Malawi.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, an alternative method which has been successfully used in low-resource settings since the 1990s is the mid-upper arm circumference (MUAC) 15–17. More recently, MUAC has been successfully used in resource-limited environments as a malnutrition screening tool for both hospitalised and critical care patients 15 18 19. Barcus et al ’s audit of nutritional status of critically ill patients in Malawi used MUAC to determine malnutrition and found 62% of adult critical care patients had moderate to severe malnutrition 14…”
Section: Introductionmentioning
confidence: 99%
“…[18-20] More recently, MUAC has been successfully used in resource limited environments as a malnutrition screening tool for both hospitalised and critical care patients. [18,21,22] Barcus et al's (2021) audit of nutritional status of critically ill patients in Malawi used MUAC to determine malnutrition and found 62% of adult critical care patients had moderate to severe malnutrition. [11]…”
mentioning
confidence: 99%